Trace elements in sedimentary pyrite track redox and nutrient fluctuations in the Ediacaran/Cambrian Bambuí Group, Brazil - Matheus Fontana de Lima (2023)
The TE variation in sedimentary pyrites, determined by the LA-ICP-MS (Laser Ablation – Inductively Coupled Plasma Mass Spectrometry) method, has the potential to provide information on different conditions of the marine environment over time. In this study, the analysis of Trace Elements in sedimentary pyrites of the Bambuí Group was carried out. What stood out most in the data set was the change in concentrations of Mo, Se, Cu, Cd, Zn, Ni and Bi in the samples from the Pedro Leopoldo Member in relation to the concentrations of these elements in the pyrites of the Serra de Santa Helena and Lagoa do Jacaré, which may indicate progressive restriction of the basin, changing from a fully connected basin to a restricted basin. The pyrite samples from the Pedro Leopoldo Member shows Mo enrichments of several hundred ppm, indicating an important, albeit transient, pulse of oxygenation as a consequence of the Marinoan glaciation. A shallow oxic layer was probably maintained until the end of the Ediacaran, during the deposition of the Lagoa Santa Member (585-540 Ma). However, radical changes in Mo concentrations and low overall micronutrient concentrations are recorded in the Serra de Santa Helena Formation, with high O² levels. This indicates the development of ferruginous waters in a sulfate-poor setting, due to the restriction of the basin by the surrounding Brasiliana mountains that formed Gondwana. The restricted conditions, poor in oxygen and depleted in nutrients, caused the disappearance of complex life forms and hindered the development of ecosystems typical of the Ediacaran-Cambrian. The reconnection of the basin may have occurred during the deposition of the Lagoa do Jacaré Formation, with greater amounts of O² in the environment. The results highlight the importance of basin restriction and connection on variations in nutrient availability during the development of Ediacaran-Cambrian ecosystems.